Numerical simulation of dryout and post-dryout heat transfer in a straight-pipe once-through steam generator. (25th July 2016) - Shi, Jianxin; Sun, Baozhi; Han, Wenjing; Zhang, Guolei; Li, Yanjun; Yang, Longbin
Highlights: Two-fluid three-flow-field model is developed to predict dryout in steam generator. The empirical correlation is used to correct dryout criterion. The interactions between three-flow-fields and the wall are considered. Dryout and post-dryout heat transfer mechanisms are discussed through the results. Abstract: Accurately predicting dryout and post-dryout heat transfer characteristics is critical for proper design of once-through steam generators. This paper provides a reasonable and simple method for this prediction by introducing a two-fluid, three-flow-field mathematical model and improving the dryout criterion-critical quality, and conducts a numerical simulation of dryout and post-dryout heat transfer in a once-through steam generator to prove the model's performance. The results show that the critical quality in a once-through steam generator is about 0.82, with the heat transfer capacity significantly reducing and the wall temperature sharply increasing in a non-linear form by approximately 30 K when dryout occurs. Part of the steam is superheated in the post-dryout region, resulting in a deviation from thermodynamic equilibrium between the vapor and liquid phases. Dryout and post-dryout heat transfer in the once-through steam generator operate between complete deviation from thermodynamic equilibrium and complete thermodynamic equilibrium. Therefore, the presence of droplets has a significant influence on the mass, momentum and energy transfer between the film and vapor phases.